EEG artifact elimination by extraction of ICA-component features using image processing algorithms - Radüntz, T.; Scouten, J.; Hochmuth, O.; Meffert, B. (Journal of neuroscience methods, 2015)
[Display omitted] •Machine-driven EEG artifact removal through automated selection of ICs is proposed.•Feature vectors extracted from IC via image processing algorithms are used.•LDA classification identifies range filter as powerful feature (accuracy rate 88%).•The method does not depend on direct recording of artifact signals.•The method is not limited to a specific number of artifacts. Artifact rejection is a central issue when dealing with electroencephalogram recordings. Although independent component analysis (ICA) separates data in linearly independent components (IC), the classification of these components as artifact or EEG signal still requires visual inspection by experts. In this paper, we achieve automated artifact elimination using linear discriminant analysis (LDA) for classification of feature vectors extracted from ICA components via image processing algorithms. We compare the performance of this automated classifier to visual classification by experts and identify range filtering as a feature extraction method with great potential for automated IC artifact recognition (accuracy rate 88%). We obtain almost the same level of recognition performance for geometric features and local binary pattern (LBP) features. Compared to the existing automated solutions the proposed method has two main advantages: First, it does not depend on direct recording of artifact signals, which then, e.g. have to be subtracted from the contaminated EEG. Second, it is not limited to a specific number or type of artifact. In summary, the present method is an automatic, reliable, real-time capable and practical tool that reduces the time intensive manual selection of ICs for artifact removal. The results are very promising despite the relatively small channel resolution of 25 electrodes.